Compatibility testing and rheological characterization in development of novel in situ guar gum-based ophthalmic dosage form - Nanjundaswamy, NG; Dasankoppa1, Fatima Sanjeri (Asian Journal of Pharmaceutics (AJP), 2014)
Guar gum is derived from the seeds of Cyamopsis tetragonolobus. Guar has certain drawbacks such as uncontrolled rate of hydration, fall in viscosity on storage, susceptibility to microbial degradation, and turbidity in aqueous dispersion. Many of these drawbacks can be overcome by using guar derivatives. Guar derivatives upon contact with water hydrate to form hydrogels for controlled-release mechanism and show stimuli-responsive changes in their structural network, and hence, the drug release. The present investigation aims at screening guar derivative (hydroxyl propyl guar) during preformulation stage by spectral (FTIR spectroscopy), thermal (differential scanning calorimetry (DSC)), isothermal (HPLC technique), and rheological characterization for the development of stable in situ ophthalmic dosage using linezolid as the model drug.